2014
DOI: 10.1287/mnsc.2013.1830
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Advertising in Magazine Markets and the Advent of the Internet

Abstract: This paper examines how the ability of media firms to engage in targeted advertising has changed with increased competition from online channels. We find that the use of the Internet by magazine readers, as well as the availability of companion websites, increase the value of targeted advertising. This indicates a complementarity between offline and online media with respect to targeting. We provide supporting evidence for this result and argue that multi-homing consumers can enhance the value of targeted adve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…And each consumer gets a gross payoff λ > 0 if she buys a relevant product. 10 With this specification, a consumer incurs a net nuisance cost of γ by viewing an irrelevant ad, and a net nuisance cost of γ − λ by viewing a relevant ad (could be net benefit if λ > γ). A location-d consumer gets a utility of β − td minus the net nuisance cost of ads if participating on platform A, and she gets a utility of β − t(1 − d) minus the net nuisance cost of ads if participating on platform B.…”
Section: Modelmentioning
confidence: 99%
“…And each consumer gets a gross payoff λ > 0 if she buys a relevant product. 10 With this specification, a consumer incurs a net nuisance cost of γ by viewing an irrelevant ad, and a net nuisance cost of γ − λ by viewing a relevant ad (could be net benefit if λ > γ). A location-d consumer gets a utility of β − td minus the net nuisance cost of ads if participating on platform A, and she gets a utility of β − t(1 − d) minus the net nuisance cost of ads if participating on platform B.…”
Section: Modelmentioning
confidence: 99%
“…As a result, when newspapers raised advertising rates (and in the process, gave incentives and made deals for national brands to advertise in multiple products and across traditional and digital platforms) they made local advertisers feel unimportant (Chandra & Kaiser, 2014). During the recession of 2008-2010, as newspapers tried to get these former advertisers back, they found that local businesses had taken their business elsewhere and found other ways to invest in marketingways that were cheaper and more effective than the printed paper (Chandra & Kaiser, 2014).…”
Section: Advertising Structurementioning
confidence: 99%
“…The result was that newspapers, which were used to consistent double-digit profit margins, bucking those raked in by Fortune 500 companies (which averaged 4 percent yields), now had to adapt to 7-to-10 percent profit margins (Gade & Lowrey, 2011). Of course, a newspaper cannot stomach diminished returns any more than an individual can stomach declining returns-oninvestment, so in the spirit of the old hierarchical structure of American media management, newspapers hedged those deflated dividends by decreasing operation and production costs (Chandra & Kaiser, 2014). Management started laying off the foot soldiers, and newspapers began running leaner operations as a way to triage the wound inflicted by the advent of the Internet and its capability to deliver more news to more people at a greater speed (Chandra & Kaiser, 2014).…”
Section: Advertising Structurementioning
confidence: 99%
See 2 more Smart Citations